Determination of blood biochemical profile of liver and kidneys in healthy alpacas (Vicugna pacos) - Flores N., Sergio (2016)
The aim of this study was to establish the blood biochemical profile of liver and kidney in clinically healthy alpacas (Vicugna pacos) of the central highlands of Peru. Blood samples (8 ml) were collected from 60 animals (30 adults and 30 tuis) by puncture of the jugular vein. The mean values were Total bilirubin: 0.62 ± 0.51 mg/dl; Direct bilirubin: 0.13 ± 0.09 mg/dl; Indirect bilirubin: 0.51 ± 0.52 mg/dl; ALT: 23.27 ± 13.11 IU/L; AST: 197.2 ± 53.74 IU; Alkaline phosphatase: 159.45 ± 76.6 IU/L; GGT: 22.35 ± 10.63; Total protein: 7.73 ± 1.18 g/dl; Albumin: 3.63 ± 0.65 g/dl; Globulin: 4.10 ± 1.40 g/dl; Urea: 39.1 ± 9.02 mg/dl; and Creatinine: 2.21 ± 0.54 mg/dl. Statistical difference was found (p<0.05) between age groups for total and indirect bilirubin and alkaline phosphatase.